A General Equilibrium Approach to Interenterprise Arrears in Transition Economies with Application to Russia - Kwon, Goohoon (IMF Working Papers; Working Paper, 1995)
This paper presents a general equilibrium model of interenterprise arrears, characterized by n-stage production technology with random productivity shocks. The model shows that large interenterprise arrears in transition economies may reflect substantial business risks in those countries and that rapid privatization and commercialization may contribute to a huge initial accumulation of trade credits and arrears. The paper also suggests that administrative measures aimed at immediate reduction of IEA such as imposition of prepayments and penalty charges, would not be as effective as partial equilibrium frameworks suggest. Consequently, a fundamental solution should be sought instead in reducing business risks or improving enterprise information. Finally, the paper discusses the relevance of the model to Russian experience in 1993 and 1994.